Social Media and Technology Across the Lifespan - Machin, Tanya; Brownlow, Charlotte; Abel, Susan; Gilmour, John. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores social media and technology across the lifespan. The authors argue that those of different ages and life stages have very diverse experiences with these types of media and demonstrate the importance of analysing the entire lifespan in the context of technology use. They acknowledge and celebrate social media for the positives that it can bring to our lives but also recognise that there may be challenges for particular developmental stages. Tanya Machin is Associate Dean in the Faculty of Health, Engineering and Sciences at the University of Southern Queensland, Australia. Charlotte Brownlow is Associate Dean of the Graduate Research School at the University of Southern Queensland, Australia Susan Abel is a sessional academic in the School of Psychology and Wellbeing at the University of Southern Queensland, Australia. John Gilmour is a Postdoctoral Research Fellow (Criminology) at The University of Queensland, Australia.
Chapter 1. Introduction - situating the scholarship and identifying the issues (Tanya Machin and Charlotte Brownlow) -- Chapter 2. Technology use of children 0-6: A diary study (Kylie Laing, Tanya Machin, Michelle Adamson, and Kristen Lovric) -- Chapter 3. Talkin' bout my generation: The utility of different age cohorts to predict antisocial behaviour on social media (Molly Branson, Evita March, and Jessica Z. Marrington) -- Chapter 4. The impact of ease of online self-expression during adolescence on identity in young adulthood (Jaimee Stuart, Riley Scott, Karlee O'Donnell, and Paul E Jose) -- Chapter 5. Communication, social support, and families (Susan Abel and John Gilmour) -- Chapter 6. Making links Between telehealth, work, and caring responsibilities (Fiona Russo and Shalene Werth) -- Chapter 7. The effects of Facebook based social support on health across metropolitan and regional Australians (John Gilmour, Carla Jeffries, Tanya Machin and Charlotte Brownlow) -- Chapter 8. What grief isn't: Dead grief concepts and their digital-age revival (Morna O'Connor and Elaine Kaskett) -- Chapter 9. Final reflections (Charlotte Brownlow and Tanya Machin).
Keywords: Psychology; Mass Media; Developmental psychology; Internet; Digital media; Cyberpsychology; Developmental Psychology; Internetpsychology; Media Psychology; Digital and New Media